Political Risk Traps In Latin America - Elizabeth Salamanca; Robyn Lynn Johnson; Francois Bernard Duhamel (European Scientific Journal, ESJ, 2016)
The purpose of this paper is to analyze salient political risks common in Latin America identifying the contexts in which they take place and the reasons for their recurrence, insofar as they affect international business investors in this region. Through a comparison of past and present political patterns in Latin America, this study assesses political risk traps, or combinations of repeatedly unforeseen political risks that international businesses may encounter in Latin American countries. The article identifies eight critical questions that investors must address looking at political risks in Latin America, as political situations faced by Latin American countries tend to be similar throughout time. It also shows the combination of political risks factors leading to a particular political risk configuration in the region. Political risks in Latin America appear over and over again because of enduring, vested interests of entrenched power groups in Latin America. Current techniques and methods to forecast country political risk are insufficient for international investors to grasp the full range of risks they may confront while investing in Latin America. Previous literature has not analyzed political risk combination and recurrence in an integrative approach. Therefore, the originality of our article is to present a framework of political risks, with a specific application to Latin America, highlighting the specific reasons for their recurrence there.